2014
DOI: 10.1073/pnas.1411696112
|View full text |Cite
|
Sign up to set email alerts
|

Recent origin of low trabecular bone density in modern humans

Abstract: Humans are unique, compared with our closest living relatives (chimpanzees) and early fossil hominins, in having an enlarged body size and lower limb joint surfaces in combination with a relatively gracile skeleton (i.e., lower bone mass for our body size). Some analyses have observed that in at least a few anatomical regions modern humans today appear to have relatively low trabecular density, but little is known about how that density varies throughout the human skeleton and across species or how and when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
168
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(201 citation statements)
references
References 49 publications
18
168
1
1
Order By: Relevance
“…This finding is consistent with recently reported results based on limb bone trabecular structure (10,26), in which significant differences in bone density were found between Holocene foragers and farmers but not between farmers and a modern industrial sample. Our results for a much more comprehensive Holocene sample indicate that moderate variation in activity level, i.e., between the Iron/Roman period and 20th century, does not affect relative bone strength significantly.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is consistent with recently reported results based on limb bone trabecular structure (10,26), in which significant differences in bone density were found between Holocene foragers and farmers but not between farmers and a modern industrial sample. Our results for a much more comprehensive Holocene sample indicate that moderate variation in activity level, i.e., between the Iron/Roman period and 20th century, does not affect relative bone strength significantly.…”
Section: Discussionsupporting
confidence: 93%
“…Earlier studies identified declines in skeletal robusticity (strength relative to body size) in Homo throughout the Pleistocene (24,25), but recent analyses suggest that the major decrease in robusticity occurred later, at the end of the Pleistocene, between early anatomically modern H. sapiens and Holocene populations (26,27). This suggestion in turn strongly implicates increased sedentism as a major driver in producing the more gracile modern human skeleton (10,25,26) and focuses attention on the Holocene as the critical period during which this transformation took place. However, the timing and pace of this change relative to major subsistence and lifestyle transitions cannot be determined from these studies, given their sparse sampling of terminal Pleistocene and Holocene populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It seems nonetheless interesting to note that, besides the ambiguous evidence from TM 1517g because of its low bone-matrix contrast, the two specimens from Swartkrans share the presence of more numerous and thick struts, locally resulting into a more closed network of plate-like structures from the accumulation of more material in the cell wall (Dalstra and Huiskes, 1995;Gibson, 1985;Stauber and Müller, 2006). At any comparable site, struts are invariably thicker in the fossil specimens than in the extant human humeri available to us, which is consistent with the process of skeletal gracilisation and trabecular bone density reduction occurred in recent humans (Chirchir et al, 2015(Chirchir et al, , 2017Ryan and Shaw, 2015). It is also noticeable that the medullary cavity of the OH 80-10 distal humerus fragment from the P. boisei partial skeleton of Olduvai Gorge, Tanzania, is filled by trabecular bone (Domínguez-Rodrigo et al, 2013).…”
Section: Discussionsupporting
confidence: 78%
“…15 Chimpanzees also exhibit a generally more robust postcranial skeleton than modern humans, who appear to exhibit systemically lower bone mass, particularly with age. 25 Thus, by including the chimpanzee calcaneus, any gross differences in cortical and trabecular bone distribution, particularly those related to potential internal partitioning of the peroneal trochlea from the calcaneal body, generated by differences in the development of this anatomy should be accounted for in the current evaluation.…”
mentioning
confidence: 99%